Mapping Persons with Disabilities (PWDs) in Indonesia Labor Market - Alin Halimatussadiah; Chaikal Nuryakin; Pyan A. Muchtar; Adriana Bella; Husnul Rizal (Institute for Economic and Social Research, 2017)
The empowerment of Persons with Disabilities (PWD) has recently attracted the attention of the Indonesian government. Several initiatives have been made to empower their life, especially the establishment of Act No. 8/2016 which enhances their right to inclusive economic activities. This study aims to map PWD in Indonesian labor market. Specifically, it analyzes the characteristics of employed and unemployed PWD. It explored Labor Force Survey (Sakernas), which began to concern on disability issue in 2016. The results show that PWD prevalence varies highly among provinces led by West Sumatera, East Nusa Tenggara, and South Sulawesi and that PWD has lower labor participation rate than that of PWOD. It may indicate the significant presence of discouraged workers among PWD.